ANALYSIS OF BIOMETHANE PRODUCTION POTENTIAL AND MITIGATION OF BIOMETHANE EMISSIONS FROM PIG FARMS IN NORTH SULAWESI PROVINCE - Manullang, Efrando; Sutaryo; Kusdiyantini, Endang (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2023)
The potential for biomethane production from livestock manure as renewable energy has good prospects, considering that the number of pigs in North Sulawesi Province increases yearly. Therefore, it is necessary to analyze the potential for biomethane production, replacing the use of LPG, and mitigate biomethane emissions from pig farms. The results showed that from 2015-2021, the most significant biomethane production was in 2021, amounting to 7,887 tons of CH4/year in the Minahasa Regency area, 2,496 tons of CH4/year (31.65%) in Tomohon City, 805 tons of CH4/year (10.20%) in South Minahasa Regency, 779 tons of CH4/year (9.88%), and in other areas 3,807 (48.27%). Biomethane can replace 8.59 million kg of Liquefied Petroleum Gas (LPG). The results of mitigating biomethane emissions in 2021 reached 34.22 Gg CO2eq, and using biomethane to replace LPG reached 11.59 Gg CO2eq. Total greenhouse gas emissions can be reduced to 45.81 Gg CO2eq. Biomethane from pig manure has promising potential as a new renewable energy and requires further investigation.